2021
DOI: 10.3389/fpsyg.2021.690384
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Institutional Care: The Forced Social Environment

Abstract: The landscape of mental health recovery is changing; there have been calls for a shift from the clinical expertise being the dominant voice within mental healthcare towards a more personalised and collaborative service that supports those in need of mental healthcare to define what recovery is for the individual. Within this new recovery movement, there has been a recognition of the importance of the social environment in which individuals are situated and the relationship of this to mental health and wellbein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 76 publications
1
5
0
Order By: Relevance
“…This may reflect this cohort's inherent struggle with social interaction due to positive and negative symptoms exacerbated by prolonged stays in psychiatric wards, an environment where social interactions are often restricted or constrained. 12,13 This study revealed a significant difference between full responders and partial responders who had an average clozapine daily dose of 466 mg and ongoing positive symptoms and were very similar to the clozapine-resistant schizophrenia patients defined by Chakrabarti. 3 The group of full responders had a notable absence of psychotic symptoms and better functioning while partial responders had ongoing positive symptoms and seriously impaired global functioning, particularly, in the social interaction domain.…”
Section: Discussionsupporting
confidence: 61%
“…This may reflect this cohort's inherent struggle with social interaction due to positive and negative symptoms exacerbated by prolonged stays in psychiatric wards, an environment where social interactions are often restricted or constrained. 12,13 This study revealed a significant difference between full responders and partial responders who had an average clozapine daily dose of 466 mg and ongoing positive symptoms and were very similar to the clozapine-resistant schizophrenia patients defined by Chakrabarti. 3 The group of full responders had a notable absence of psychotic symptoms and better functioning while partial responders had ongoing positive symptoms and seriously impaired global functioning, particularly, in the social interaction domain.…”
Section: Discussionsupporting
confidence: 61%
“…The Therapeutic Community model creates an environment in which everyday constructions of hypermasculinity can be challenged and new constructions of hegemonic masculinity can be embraced and supported, by all community members including staff. Our previous paper advocated for the Therapeutic Community model within forensic environments in response to the challenging interpersonal environment in which racism, violence and bullying was observed by the ethnographer ( 4 ). Once again, this model is advocated for, particularly within the context where individuals are undertaking rehabilitative work related to sexual offending, so that everyday social encounters can be underpinned by an egalitarian ethic, one that challenges the gender inequalities which pervade social life and indeed our institutions, and contribute to the continuum and the continuation of VAWG.…”
Section: Discussionmentioning
confidence: 99%
“…A commitment to such notions of masculinity serves to marginalise those who do not fit the social norms of masculinity ( 83 ) and this commitment may indeed have been performed within the institutional community. Racial abuse experienced by staff and those in receipt of care is prevalent within the forensic mental health context ( 4 ), thus intersectionality would undoubtedly be relevant to the arguments presented within this paper.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations